GENETIC AND NON GENETIC PARAMETERS FOR BODY WEIGHTS OF TWO IRAQI LOCAL CHICKNS - & Abdullah, Hermiz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study aimed to investigate the genetic parameters for body weights of White and Black local chickens. The experiment conducted at College of Agric., Salahaddien Univ. during the period from Sept. 2016 until April 2018. 520 fertile eggs were taken from Agri. Res. Center, Ministry of Agric., Baghdad. Hatched chicks considered as parents (G0), and distributed randomly in to ten families. Resulted eggs from each family were collected during the peak of production for each generation to produce chicks of the next generation (G1 and G2). Body weights of resulted chicks were recorded at 1-day old and weekly till maturity. SAS program used to analyze the body weights (BW) and body weight gains (BWG) at different ages. The model includes genetic groups and generations for traits before sexing and the effect of sex added for the traits after sexing. Variance component of random effects estimated by REML and tested for positive definiteness to develop reliable estimates. Repeatability for body weights estimated. BW of chicks at 1 day, 4, 8, 9, 10, 16 and 17 week were 31.02, 292.47, 679.29, 794.58, 892.82, 1362.53 and 1252.17 g, and BWG at (1-4, 4-8, 9-10 and10-16) weeks were 261.45, 386.82, 98.24, and 469.51 g, respectively. The chicks of black group significantly excelled the white group in their weight at 1 day, 4, 8, 16 and 17, as well at ages 1-4 and 10-16 weeks. The effect of generation on BW of chicks at all ages and BWG at 1-4, 4-8 weeks was highly significant and (P